Effect of hand exercises on grip strength and manual dexterity in children with severe congenital visual impairment - Sumayya Faiz Shaikh, (Indian Journal of Child Health, 2020)
Background: Vision is important in planning and performing motor skills. Early reduction or lack of visual function may alter or delay the development of basic motor and visual-motor skills. Developing skilful hands is a necessity in blind children as it often compensates for their missing vision. Objective: The objective of the study was to focus on the efficacy of hand exercises on grip strength and manual dexterity in children with severe congenital visual impairment. Materials and Methods: The study included 60 children aged 7–15 years who were diagnosed with severe bilateral congenital visual impairment. Hand exercises were given to all the 60 children at least 4 days in a week for a period of 6 weeks. Grip strength and manual dexterity values were analyzed using Jamar dynamometer and Purdue Pegboard test, respectively. Results: The mean age was 12.15±2.284 years. We observed a significant improvement in grip strength (p